DEVELOPMENT OF PBL LEARNING MODEL BASED ON "NEWS REPORT" WITH CANVA MEDIA ON PKN LESSONS - Roudhotul Jannah; Inzanul Kamil (International Jurnal of Education Schoolars, 2021)
Along with the increasingly advanced development of information and communication technology today requires every human being, especially in the field of education to continue to improve their professionalism, especially in terms of developing learning innovations that can be in the form of models, media, etc. developed. In this paper, it is concluded that the author is trying to develop a news-hassle-based PBL learning model using Canva media with many studies discussed such as the definition of Civics learning, learning media, learning models, development of learning models, PBL learning models, learning development models. With this development, it is expected to be able to answer the problems that have arisen in the world of education so far because it is felt that the learning used is more interesting and innovative so that it will be motivated and enthusiastic in participating in lessons, especially Civics lessons.